3D microsimulation of milkruns and pickers in warehouses using SIMIO - Vieira, António Amaro Costa (2014)
To help the Bosch Car Multimedia Portugal in Ferreiros, Braga to reduce its costs (both in time and space) with its warehouse, a micro simulation model is being developed in Simio. Particularly, the tool needs to be able to model pickers riding milkruns to collect containers of products, from a warehouse, to satisfy the needs of the production lines. In this sense, the storage strategy used on the warehouse, the quantity of requests a picker gets per shift, the time between shifts, the number of types of products, the arrival rate of requests, and the number of milkruns and pickers needs to be adjustable. Additionally, to design the corridors of the warehouse in a configurable way, an Add-in in C#, using the API of Simio, is being developed. Thus, this paper intends to document the first part of the simulation model developed, which consists on the pickers receiving requests and riding their milkruns to collect the respective containers from the warehouse. Five different Simio models compose the main simulation model. Conclusions and future work are discussed.